Hubungan Sikap Dan Konsumsi Tablet Fe Dengan Kejadian Anemia Pada Remaja Putri Di Smp N 6 Tapung Kecamatan Tapung Kabupaten Kampar Tahun 2023 - Naldaroza, Sari; Harahap, Dewi Anggriani; Syahda, Syukrianti (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
Juvenile anemia is where the amount of hemoglobin in the blood is less than normal, namely <12g/dL, anemia occurs when the body does not have enough erythrocytes, this causes the body to produce too few erythrocytes and the use of erythrocytes increases. Factors that can cause the high incidence of anemia in adolescent girls are, lack of intake of iron and other nutrients, for example vitamin A, vitamin C, folate, vitamin B12. The aim is to determine the relationship between attitudes and consumption of Fe tablets with anemia in adolescent girls in SMP N 6 Tapung. This type of research uses quantitative, analytical research with a cross sectional design. The population in this study was all 100 young women in classes 1 and 2 of SMP Negeri 6 Tapung. The sample in this study used a total sampling technique, namely 100 young women in classes 1 and 2 of SMP Negeri 6 Tapung. The analysis in this study was univariate and bivariate analysis. The results of this study found a relationship between attitudes and the incidence of anemia in adolescent girls with a p value = 0.002, and there was a relationship between consumption of Fe tablets and the incidence of anemia in adolescent girls with a p value = 0.001. It is recommended to schools that the results of this research can be used as material for consideration in taking early action in disseminating information to teenage female students, regarding the importance of health in order to improve the quality and integrity of female students in carrying out their education.